2006
DOI: 10.1136/ard.2005.039842
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II, tumour necrosis factor  , and lymphotoxin   gene haplotype associations with serological subsets of systemic lupus erythematosus

Abstract: The strongest association in this predominantly white population with SLE was between HLA-DR3 and anti-La, which seemed to account for any associations with TNFalpha alleles on an extended DR3 haplotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 43 publications
4
41
1
2
Order By: Relevance
“…The subjects of the study by McHugh et al [16] were mainly Caucasians, and the study was included in Caucasian population when stratifying by ethnicity. The allele and the genotype frequencies of the TNF-a promoter 2 238A/G polymorphism were extracted from 10 of the 11 eligible studies, while only G/A þ A/A and G/G genotypes were extracted from the study by Rood et al [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects of the study by McHugh et al [16] were mainly Caucasians, and the study was included in Caucasian population when stratifying by ethnicity. The allele and the genotype frequencies of the TNF-a promoter 2 238A/G polymorphism were extracted from 10 of the 11 eligible studies, while only G/A þ A/A and G/G genotypes were extracted from the study by Rood et al [20].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining nine studies were retrieved for more detailed Meta-analysis of TNF-a promoter 2 238A/G 267 evaluation [14,15,17 -23]. One additional study was identified by reviewing the references of these studies [16]. Meanwhile, we excluded one study due to duplicate report [23].…”
Section: Resultsmentioning
confidence: 99%
“…Genetic and epidemiological findings have strongly implicated polymorphic sites within MHC class II molecules in the pathogenesis of autoimmune diseases. [26][27][28] Recently HLA-DRB1*11 has been identified as a risk factor for the development of acquired TTP. It has been observed that the HLA-DRB1*11 is more frequent in patients with acquired TTP when compared with a control population.…”
Section: Introductionmentioning
confidence: 99%
“…A strong association between HLA class II alleles and SLE was demonstrated by McHugh et al in 2006 (20). One of the suggested pathogenetic mechanisms of HLA class II molecules in SLE is their contribution to activation of CD4+ T cells.…”
Section: Discussionmentioning
confidence: 96%